Geochemical Characteristics of Elements and Main Controlling Factors of Organic Matter Enrichment in Shale from Wufeng Formation to Submember Long-11 in Southern Sichuan - Rong Xiong; Quan Zhong; Zhenxing Ren (Applied Sciences, 2023)
A total of 70 shale samples from seven core holes, namely, N203, N208, N209, N210, N211, N215 and N217, in Changning area, south Sichuan, were analyzed for major and trace elements. Based on an analysis of longitudinal variation characteristics of major and trace elements, the REDOX conditions, paleoproductivity, relative sea level height and terrigenous detrital injection amount of gas-bearing shale in Wufeng Formation–Submember Long-11 in the Changning area were studied. And, the main controlling factors of organic matter enrichment in Wufeng Formation–Submember Long-11 were discussed. The results show the following: (1) Trace elements Mo, U, Ba and Ni are relatively enriched in the shale of Wufeng Formation–Submember Long-11 in the Changning area, while the Co element is deficient. The flat distribution pattern of rare earth in Wufeng Formation–Submember Long-11 shows that the shale deposits are weakly influenced by terrigenous materials. The amount of terrigenous injection in Wufeng Formation is higher than that in Submember Long-11, and the amount of terrigenous injection increased gradually from the lower part of Bed Long-111 to the lower part of Bed Long-114. (2) The REDOX environment discrimination indexes such as U/Th, Ni/Co, V/Sc and δU show that the water REDOX conditions of Wufeng Formation–Submember Long-11 in the Changning area have changed many times during the shale sedimentary period, and the overall REDOX conditions are dominated by an anaerobic environment. The REDOX indexes at the boundary between Long-111 and Wufeng Formation are relatively small and in the oxidizing environment range. The REDOX index from Bed Long-111 to Bed Long-114 decreases gradually, and the anaerobic environment of Bed Long-111 and Bed Long-112 gradually changes to the oxygen-poor environment of Bed Long-113; and, the REDOX index of Bed Long-114 is the lowest, which is generally oxygen rich. (3) Organic matter enrichment in Wufeng Formation Submember Long11 in the Changning area is mainly controlled by REDOX conditions. Low terrigenous injection and a relatively high sea level have positive effects on organic matter enrichment, but there is no obvious relationship between the paleoproductivity and organic matter enrichment.